Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
[tex]y-y_1=m(x-x_1)\\\\
y-(-6)=-\dfrac{1}{2}(x-6)\\
y+6=-\dfrac{1}{2}x+3\\
y=-\dfrac{1}{2}x-3[/tex]
[tex]You\ can\ just\ plug\ this\ into\ point-slope\ equation: \\ (y-y1)=m(x-x1)\ \ \ \ m\ is\ slope \\ \\ (y-(-6)= \frac{-1}{2}(x-6) \\ \boxed{y+6= \frac{-1}{2}(x-6) } \\ \\ If\ you\ want\ in\ slope-intercept\ form: \\ y+6= \frac{-1}{2}(x-6) \\ y+6= \frac{-1}{2}x+3 \\ \boxed{ y=- \frac{1}{2}x-3 }[/tex]
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.